Analisis Kontribusi Sektor Pertanian Terhadap PDRB Kabupaten Kepulauan TanimbarAnalisis Kontribusi Sektor Pertanian Terhadap PDRB Kabupaten Kepulauan Tanimbar: Paulus Laratmase, Mesak Y. Masela, Moses Feninlambir*, Lukas Batdjedelik - Paulus Laratmase; Mesak Y. Masela; Feninlambir, Moses; Lukas Batdjedelik (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2023)
The agricultural sector plays an important role in the economic growth of a region. The Tanimbar Islands Regency has the potential to contribute to the agricultural sector. This research aims to analyze the contribution of the agricultural sector to the PDRD of the Tanimbar Islands Regency which includes the development of the GDP growth rate, the role of the agricultural sector in regional economic development of the Tanimbar Islands Regency, problems and agricultural development systems in the Tanimbar Islands Regency. In this research, generally the data used is secondary data, namely ready-to-use data that has been processed by other parties, in the form of reports/documents obtained from related agencies, so the data source in this writing is the Department of Agriculture and Fisheries. Maritime Affairs and BPS KKT. The analytical method is useful for determining the contribution of the agricultural sector to the KKT GRDP in 2015-2020. The analytical method used is a descriptive method with a contribution approach. The results of this research show that the GDP growth rate of the Tanimbar Islands Regency for the 2016-2020 period, both based on Current Prices and Constant Prices, always experiences very good upward fluctuations (2016-2019), but this is different in 2020, experiencing slow economic growth, namely above The applicable price base is 1.05%. Meanwhile, based on constant prices, the rate of economic growth experienced stagnation, namely - 0.02%. This happened due to a non-natural global phenomenon, namely the Covid'19 (Corona Virus) Pandemic. The contribution of the Agricultural sector to the GRDP of the Tanimbar Islands Regency for the period 2016 - 2020 averaged above 20%, this shows that the Agricultural sector is one of the sectors with quite large potential to have dominant value (added) for the formation of income (GRDP) in the Tanimbar Islands Regency.